Fabrication and Mechanical Characterization of Glass and Carbon Fibre Reinforced Composite’s Used for Marine Applications - Sarath Chandra, D.; K.Vijaya Kumar Reddy, Dr.; Omprakash Hebbal, Dr. (International Journal of Engineering and Technology, 2018)
The composite materials are replacing the traditional materials, because of its superior properties such as high tensile strength, low thermal expansion, high strength to weight ratio. The developments of new materials are on the anvil and are growing day by day. Fiber composites such as Glass-Fiber Reinforced Polymers (GFRP) composites and Carbon-Fiber Reinforced Composites (CFRP) became more attractive due to their better properties for marine applications. In this paper, GFRP, CFRP and Hybrid composites are developed and their mechanical properties such as Hardness, tensile strength, compression strength, impact strength, toughness are evaluated. The study used to compare the effect volumetric fraction of fibers in order to improve strength and toughness, this done by using two types of fibers E-glass and carbon & two types of resins epoxy ( AralditeLY556 and Aradur HY951 ) and vinyl ester. In this experimental study, we found that high tensile strength, high specific strength, hardness and low density are obtained with carbon fibre reinforced composites, but high impact strength and toughness are obtained with glass fibre reinforced composites. Finally incorporate the result and try to find alternatives composites using for marine applications and obtain the best mechanical properties